Targeting tumor microenvironmental barriers to enhance immunogenic cell death in solid tumors - Zhang, Jifeng; Han, Wei; Zhang, Mingchen; Yi, Yingjie; Long, Mei (Frontiers in Immunology, 2025)
Immunogenic cell death (ICD) effectively triggers adaptive immune responses against cancer, yet its clinical application in solid tumors is hindered by tumor microenvironment (TME) barriers. These include immunosuppressive cell populations, dense extracellular matrix, abnormal vasculature, hypoxia, and metabolic suppression, which collectively impede immune infiltration and function. This review evaluates current therapeutic strategies to overcome these barriers, including vascular normalization (restoring abnormal tumor blood vessels to a more structured and functional state to improve perfusion and immune cell infiltration), extracellular matrix (ECM) modulation, alleviation of hypoxia, metabolic reprogramming, immunosuppressive cell targeting, physical remodeling, and nanoparticle-based drug delivery. Clinical evidence highlights the potential of these integrated approaches to enhance ICD-induced antitumor immunity, suggesting promising avenues for improving patient outcomes through combined modulation of the TME and ICD induction.